Caitlyn L.

asked • 02/26/17# Factorising

^{4}-13a

^{2}+3b

## 3 Answers By Expert Tutors

Guiyou Q. answered • 02/26/17

A math lover for life

^{4}- 13a

^{2}+36=(a

^{2}-9)(a

^{2}-4)

Andrew M.

^{4}- 13a

^{2}+ 36

^{2}

^{2}- 13u + 36

^{2}

^{2}-9)(a

^{2}-4)

02/27/17

Arturo O. answered • 02/26/17

Experienced Physics Teacher for Physics Tutoring

^{2}and get a quadratic expression.

^{4}- 13a

^{2}+ 3b = y

^{2}- 13y + 3b = (y + A)(y + B) = (a

^{2}+ A)(a

^{2}+ B)

Andrew M. answered • 02/26/17

Mathematics - Algebra a Specialty / F.I.T. Grad - B.S. w/Honors

^{4}-13a

^{2}+3b

^{4}- 13a

^{2}

^{4}= (a

^{2})

^{2}

^{2}= [(√13)a]

^{2}

^{4}- 13a

^{2}+ 3b = (a

^{2}- (√13)a)(a

^{2}+ (√13)a) + 3b

## Still looking for help? Get the right answer, fast.

Get a free answer to a quick problem.

Most questions answered within 4 hours.

#### OR

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.

Michael J.

02/26/17